Combined use of synchrotron radiation based micro-X-ray fluorescence, micro-X-ray diffraction, micro-X-ray absorption near-edge, and micro-fourier transform infrared spectroscopies for revealing an alternative degradation pathway of the pigment cadmium yellow in a painting by Van Gogh - Van der Snickt, Geert; Janssens, Koen; Dik, Joris; De Nolf, Wout; Vanmeert, Frederik; Jaroszewicz, Jacub; Cotte, Marine; Falkenberg, Gerald; Van der Loeff, Luuk (Analytical chemistry (Washington), 2012)
Over the past years a number of studies have described the instability of the pigment cadmium yellow (CdS). In a previous paper we have shown how cadmium sulfide on paintings by James Ensor oxidizes to CdSO(4)·H(2)O. The degradation process gives rise to the fading of the bright yellow color and the formation of disfiguring white crystals that are present on the paint surface in approximately 50 μm sized globular agglomerations. Here, we study cadmium yellow in the painting "Flowers in a blue vase" by Vincent van Gogh. This painting differs from the Ensor case in the fact that (a) a varnish was superimposed onto the degraded paint surface and (b) the CdS paint area is entirely covered with an opaque crust. The latter obscures the yellow color completely and thus presents a seemingly more advanced state of degradation. Analysis of a cross-sectioned and a crushed sample by combining scanning microscopic X-ray diffraction (μ-XRD), microscopic X-ray absorption near-edge spectroscopy (μ-XANES), microscopic X-ray fluorescence (μ-XRF) based chemical state mapping and scanning microscopic Fourier transform infrared (μ-FT-IR) spectrometry allowed unravelling the complex alteration pathway. Although no crystalline CdSO(4) compounds were identified on the Van Gogh paint samples, we conclude that the observed degradation was initially caused by oxidation of the original CdS pigment, similar as for the previous Ensor case. However, due to the presence of an overlying varnish containing lead-based driers and oxalate ions, secondary reactions took place. In particular, it appears that upon the photoinduced oxidation of its sulfidic counterion, the Cd(2+) ions reprecipitated at the paint/varnish interface after having formed a complex with oxalate ions that themselves are considered to be degradation products of the resin and/or oil in the varnish. The SO(4)(2-) anions, for their part, found a suitable reaction partner in Pb(2+) ions stemming from a dissolved lead-based siccative that was added to the varnish to promote its drying. The resulting opaque anglesite compound in the varnish, in combination with the underlying CdC(2)O(4) layer at the paint/varnish interface, account for the orange-gray crust that is disfiguring the painting on a macroscopic level. In this way, the results presented in this paper demonstrate how, through a judicious combined use of several microanalytical methods with speciation capabilities, many new insights can be obtained from two minute, but highly complex and heterogeneous paint samples.